The impact of HIV/AIDS on elderly people in the Thulamela Municipality, Vhembe District, Limpopo Province - Singo, Vhudivhusi Julia (My University, 2013)
HIV/AIDS causes serious burdens on the lives of elderly people, and more particularly so because they are often expected to take care of their terminally ill children and assume the responsibility of looking after children orphaned by HIV/AIDS, in most cases with very little resources. The overall aim of this study was to explore and describe the impact of HIV/AIDS on elderly people infected with and/or affected by HIV/AIDS (EPLWHA) in the Thulamela municipality. The study sought to achieve the following objectives: describing the views of elderly people regarding the impact of HIV/AIDS on their lives, determining the challenges that EPLWHA face in their daily lives, and gaining a sense of the coping strategies they use to overcome the obstacles they face in relation to HIV/AIDS. Ethical issues such as permission to conduct the study, informed consent, confidentiality and anonymity, withdrawal of participation and measure to ensure trustworthiness were taken into consideration. A qualitative explorative descriptive study was conducted in two phases. During the first phase, key participants were interviewed using an interview guide.. In the second phase, general participants were interviewed, also using an interview guide. Information provided by the participants was captured on a tape recorder. Data collected during interviews over a period of three weeks, with key participants and general participants, were collated into themes, categories and subcategories. The data were analyzed using an open coding method. The study findings revealed that HIV/AIDS has serious negative impacts on the lives of elderly people, particularly those living in poverty. The following key areas in relation to EPLWHA were established: psychological or emotional health, household and socioeconomic burdens. Considering the role that elderly people plays in the community insofar as HIV/AIDS is concerned, primary health promotion and social welfare programmes should be directed at educating all elderly people and their service providers how to cope with the health and social problems related to HIV/AIDS.
MPH
Department of Public Health
Keywords: HIV; UCTD; AIDS; Elderly people; Old age; HIV infected orphans; 362.19697920968257; HIV infections -- South Africa -- Limpopo; HIV positive persons -- South Africa -- Limpopo; AIDS (Disease) in old age -- South Africa -- Limpopo; AIDS (Disease) -- Patients -- South Africa -- Limpopo